Acute kidney injury in patients undergoing endovascular therapy for critical limb ischemia. Issue 4 (16th August 2019) - Prasad, Anand; Hughston, Haley; Michalek, Joel; Trevino, Aron; Gupta, Kamal; Martinez, John P.; Hoang, Dale T.; Wu, Patrick B.; Banerjee, Subhash; Masoomi, Reza
Abstract: Background: Similar to coronary angiography and interventions, patients undergoing percutaneous treatment of lower extremity peripheral arterial disease are also at risk of acute kidney injury (AKI). The incidence, risk factors associations, need for dialysis and inhospital mortality related to AKI in patients with critical limb ischemia (CLI) following endovascular therapy is poorly defined. Objectives: The purpose of this study was to analyze data from the National Inpatient Sample (NIS) to determine the aforementioned outcomes in patients with CLI. Methods: Using the full NIS admission dataset from 2003 through 2012, ICD‐9 codes relevant to comorbid conditions, procedure codes, composite codes for AKI, and inhospital mortality were analyzed using multivariate models. Results: A total of 273, 624 patients were included with a mean age of 70.0 ± 27.4 years, 46.0% were female, 57.2% had diabetes, 43.4% had coronary artery disease (CAD), and 29.2% had chronic kidney disease (CKD). The overall rate of AKI was 10.4%, and there was a temporal rise over the analysis period in AKI incidence ( p < .001). Age, diabetes, CKD, and heart failure were all associated with AKI ( p < .0001). The inhospital mortality rate in the patients with AKI declined over time but was higher than in patients without AKI (6.0% vs. 1.4%), p < .0001. The mortality rate was substantially higher in patients with AKI requiring dialysis as compared to AKI not requiring dialysis (13.4% vs. 5.6%), p < .0001. Conclusions: AKI is associated with age, CKD, and heart failure. The incidence of AKI following endovascular therapy for CLI is rising and independently associated with inhospital mortality.